Multi-age schooling : an information package for parents and educators - Norman, Tony R., 1961- (2001)
Thesis (M.Ed.)--Memorial University of Newfoundland, 2002. Education Bibliography: leaves 29-31.The CD-ROM contains the Multi-Age Information Resource (MAIR) documents and weblinks. This thesis has no abstract